BOOK REVIEW: IMPOVERISHMENT OF MADURESE SALT FARMERS - Putut Jonggolelono (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Title : Sosiologi GaramAuthor : Iskandar DzulkarnainEditor : Ragil Cahya MaulanaPublisher : Cantrik PustakaISBN : 978-623-6063-87-3Year : 2023